2020
DOI: 10.1016/j.cplett.2020.137869
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical simulation of Chloroquine drug interaction with C60 fullerene for treatment of COVID-19

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…The COVID-19 illness causes high mortality due to severe respiratory syndrome. Up till now, because of enhancement of coronavirus epidemic in entire of world, several clinical research groups are investigating the remedial choices for control of COVID-19 illness [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 illness causes high mortality due to severe respiratory syndrome. Up till now, because of enhancement of coronavirus epidemic in entire of world, several clinical research groups are investigating the remedial choices for control of COVID-19 illness [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical and antiviral effectiveness of Remdesivir in COVID-19 illness remains to be recognized [7][8][9][10][11][12]. In order to improve therapeutic efficiency of Remdesivir drug, the use of nano medicine and design of drug delivery vehicles based on nanomaterials, which may increase efficiency of absorption of drugs, is important [6,13].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental investigation on new material is also essential but they are time-consuming and costly and do not give enough information. Therefore, computational work has been employed to understand the nature of interaction and its mechanism (Hazrati and Hadipour 2016a , b ; Novir and Aram 2020 ). Some of the important chemical properties such as binding energy (E b ), energy gap (E g ), electrophilicity indexes (ω), chemical hardness (η), the electronegativity of a system (χ), and maximum electronic charge (ΔN max ), density of states (DOS) and molecular electrostatic potential maps (MEPS) have been calculated in this work.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of several double bonds is responsible for scavenging free radicals [ 20 ] and probably for establishing strong non-covalent interactions between fullerenes and the various residues of the spike protein and the hACE2 receptor. Moreover, it has been showed that the hydroxychloroquine [ 21 ] and adsorption of chloroquine on C60 fullerenes and the doped one with B, Al and Si are thermodynamically stable [ 22 ] and are potential carriers of drugs [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent experimental [ 26 ] study showed that the lipid layer present in the virus of COVID-19 can be deactivated by the nanocarbon-coated surfaces, such as fullerenes. Other studies showed anti-cancer effects of fullerene derivatives [ 27 29 ]. Herein, our work reports the exploitation of the electronic and structural characteristics of fullerenes and the examination of their interactions with the spike protein and hACE2 receptor.…”
Section: Introductionmentioning
confidence: 99%